2006
DOI: 10.1007/s00775-006-0139-0
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-cleaving catalyst selective for melanin-concentrating hormone: oxidative decarboxylation of N-terminal aspartate catalyzed by Co(III)cyclen

Abstract: To provide a firm basis for the new paradigm of drug discovery based on catalysts for oxidative cleavage of N-terminal aspartate (Asp) residues of oligopeptides, oligopeptide-cleaving catalysts were searched by using melanin-concentrating hormone (MCH) as the substrate. MCH is a target for designing drugs to reduce obesity. Catalyst candidates containing the Co(III) complex of cyclen as the catalytic center were prepared by multicomponent condensation reactions. From three kinds of chemical libraries containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…9 The dependence of k o and C o for the catalytic activity of B was measured at pH 8.0 and the results are illustrated in Figure 3. The kinetic data of Figure 3 can be analyzed in terms of the Michaelis-Menten scheme as performed previously 9 with the MCH cleavage catalyzed by A. The linear dependence is consistent with very weak complexation between MCH and B (K m >> S o ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…9 The dependence of k o and C o for the catalytic activity of B was measured at pH 8.0 and the results are illustrated in Figure 3. The kinetic data of Figure 3 can be analyzed in terms of the Michaelis-Menten scheme as performed previously 9 with the MCH cleavage catalyzed by A. The linear dependence is consistent with very weak complexation between MCH and B (K m >> S o ).…”
Section: Resultsmentioning
confidence: 99%
“…, pseudo-first-order kinetic behavior is to be observed. 9 Since the concentration of MCH decreased slowly even in the absence of catalysts, 9 the background rate was subtracted to estimate pseudo-first-order rate constants (k o ). The pH dependence of k o measured at a fixed C o (Figure 2) showed that the optimum activity was manifested at pH 8.0.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,7,[11][12][13][14][15][16][17][18][19] The present study indicates that the target-selective artificial proteases may be especially effective for amyloidoses such as Alzheimer's disease, diabetes, Parkinson's disease, Huntington's disease, and mad cow's disease for which the conventional drugs targeting active sites of proteins cannot be designed.…”
mentioning
confidence: 99%